PENINGKATAN KOMPETENSI GURU DALAM PENYUSUNAN MODUL AJAR INOVATIF MELALUI WORKSHOP BERKELANJUTAN DAN DAMPAKNYA TERHADAP LEARNING SURPLUS SISWA - Mawardi, Mawardi; Hardini, Agustina Tyas Asri; Yulia, Hanita (LPPM Universitas Bina Bangsa, 2024)
The priority problems to be solved in this service include two problems. The first problem is that the Teaching Modules prepared by teachers in partner schools are not innovative. The second problem is that learning practices have not applied learning technology according to the demands of 21st century learning, so they are unable to achieve student's learning surplus. The first solution is to conduct workshops to improve teachers' insights and skills about the urgency of lesson plans in learning, learning components, designing innovative learning models, developing learning videos, and conducting peer teaching. The second solution, through learning (realteaching) in the classroom using innovative Teaching Modules that have been prepared with technology assistance according to the demands of 21st century learning. This PkM method uses a continuous workshop model. Data collection instruments used tests and interviews. The data analysis technique uses descriptive percentage and categorical techniques. The results of PkM stated that the competence of elementary school teachers in the Kenanga Cluster in preparing Innovative Teaching Modules assisted by 21st century learning technology was in the good category. Learning practices using innovative teaching modules have an impact on the growth of student's learning surplus